What happens when we die : a psychic's exploration of death, heaven, and the soul's journey after death - Bodine, Echo L. (New World Library, 2013)
"A guide to understanding our souls, during life and after death, from a psychic. Includes practical advice for being with those who are dying and for cultivating clear communication with the deceased"--